KIẾN THỨC VỀ ĐÁI THÁO ĐƯỜNG TÍP 2 CỦA NGƯỜI BỆNH NGOẠI TRÚ TẠI BỆNH VIỆN LÊ VĂN THỊNH NĂM 2026 (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine diabetes knowledge scores among patients with type 2 diabetes at Le Van Thinh Hospital in 2026 using the DKQ-R and to describe the percentage of correct responses by item and topic domain.Methods: A cross-sectional descriptive study was conducted on 106 patients with type 2 diabetes receiving outpatient care at the Family Medicine Clinic of Le Van Thinh Hospital, Ho Chi Minh City, in January 2026. Diabetes knowledge was assessed using the 22-item DKQ-R with a yes/no/don’t know response format, yielding total scores of 0–22. Correct response rates by item and topic domain were analyzed based on the original author's classification.Results: The mean age was 60.7 ± 11.2 years; 61.3% were female. The mean DKQ-R score was 12.7 ± 3.3 (equivalent to 57.7%), with acceptable internal consistency (KR-20 = 0.664). The highest correct response rates were in blood glucose symptoms (70.3%) and complications (69.1%). The lowest were in foot/eye/dental care (18.4%), vaccination (34.9%), and nutrition (50.7%).Conclusions: Diabetes knowledge among patients was not optimal, with notable gaps remaining in several important domains, particularly foot, eye, and dental care, as well as vaccination.
Keywords: diabetes knowledge, DKQ-R, type 2 diabetes, family medicine, health education.